Risk assessment of two new pesticides based on the intestinal fungal community construction and growth status of predatory insects (Arma custos) - Yang, Xue; Xu, Fei; Zhang, Baoshan; Huang, Maojin; Zhang, Guocai (Frontiers in Microbiology, 2025)
This study aims to conduct a comprehensive safety assessment of two novel pesticides—tetraniliprole (SZ) and Metarhizium anisopliae (LJ)—with the goal of providing scientific data to underpin the refinement of current risk assessment frameworks for new pesticides and guiding the optimization of field application strategies. Using the predatory insect A. custos as a model organism, we designed negative control (CK) and concentration-gradient experiment to investigate the effects of these pesticides on the physiological indices and growth performance of A. custos. Additionally, we analyzed their impacts on the structural and functional characteristics of the intestinal fungal community in A. custos, as well as the interaction mechanisms between gut fungi and host physiological-biochemical processes. The results showed that: (1) at 72 h post-pesticide application, the body weight growth rate of A. custos was higher in the SZD and SZG groups than in the control (CK), with the order SZD > SZG > CK; similarly, the LJG and LJD groups also exhibited higher growth rates than CK, following LJG > LJD > CK. (2) By 120 h post-application, the survival rate of CK was higher than that of the SZD and SZG groups (CK > SZG > SZD), and also higher than that of the LJG and LJD groups (CK > LJG > LJD). (3) The abundance of M. anisopliae was positively correlated with the activities of catalase (CAT), carboxylesterase (CarE), superoxide dismutase (SOD), glutathione S-transferase (GST), and acetylcholinesterase (AChE) in A. custos (p < 0.05). Conversely, tetraniliprole was negatively correlated with CAT and CarE activities (p < 0.05). (4) Deterministic ecological processes were the dominant drivers shaping the assembly of the intestinal fungal community in A. custos under the LJ and SZ treatments. (5) In the LJ treatment group, M. anisopliae absolutely dominated the intestinal fungal community, suppressing the growth of other fungal taxa. In the SZ group, environmentally widespread species such as Candida parapsilosis and Aspergillus penicillioides became characteristic intestinal fungal groups. In conclusion, M. anisopliae showed higher safety for predatory insects compared to tetraniliprole. These findings facilitate the construction of more robust risk assessment frameworks for novel pesticides and provide theoretical insights for promoting sustainable agricultural practices within the ecological civilization development paradigm.